A Case of Ischemic Stroke Associated with Internal Carotid Artery Dissection Due to Penetrating Trauma: Medico Legal Evaluation for Causality - Asirdizer, Mahmut; Arslan, Mehmet; Demir, Ugur (The Bulletin of Legal Medicine, 2019)
Ischemic stroke is an important cause of morbidity and mortality. However, ischemic stroke due to traumatic internal carotid artery dissection is a rare medical condition.In this case report, a 35-year-old male patient was injured with a stab in the neck and total aphasia and right hemiparesis occurred in him. In radiological examinations, brain infarction in the left parieto-temporal region and internal carotid artery dissection following stabbing were diagnosed.In the medico-legal evaluation of this case in the forensic medicine department, case consulted with neurosurgery department for to exclude “the presence of another traumatic or pathological condition” and to establish the causality between “carotid artery injury due to stabbing” and “stroke and aphasia causing ischemia”.Because of the case presented in this article, the literature was reviewed, the concept and procedure of causality in forensic medicine applications was discussed and the importance of multidisciplinary approach was emphasized in such cases.
Keywords: Carotid artery injury; stroke; aphasia; brain ischemia; casuality